3D bioprinting in tissue engineering and regenerative medicine - Gupta, Sharda; Bit, Arindam (Cell and tissue banking, 2022)
This review paper is primarily focused on bioprinting technology for biomedical applications. Bioprinting can be utilized for fabrication of wide range of tissue, based on which this chapter describes in detail its application in tissue regeneration. Further, the difficulties and potential in developing a construct for tissue regeneration are discussed herein. In this review paper, application of 3D bioprinting in tissue regeneration will be discussed in depth.